Giải chi tiết ạ.

Report
Question

Please briefly explain why you feel this question should be reported.

Report
Cancel

Giải chi tiết ạ.

Answers ( 1 )

  1. Please briefly explain why you feel this answer should be reported.

    Report
    Cancel

    Đáp án+Giải thích các bước giải:

    `P = ( ( x – 2 )/( x + 2√x ) + 1/( √x + 2 ) ) : ( √x – 1 )/( √x + 1 )`   với  `x > 0 ; x` $\neq$  `1`

    `P = (  ( x – 2 )/( √x( √x + 2 )) + ( √x )/( √x( √x + 2 )) ) . ( √x + 1 )/( √x – 1 )`

    `P = ( x + √x – 2 )/( √x( √x + 2 )) . ( √x + 1 )/( √x – 1 )`

    `P = ( x – √x + 2√x – 2 )/( √x( √x + 2 )) . ( √x + 1 )/( √x – 1 )`

    `P = ( √x( √x – 1 ) + 2( √x – 1 ))/( √x( √x + 2 )) . ( √x + 1 )/( √x – 1 )`

    `P = ( ( √x + 2 )( √x – 1 ))/( √x( √x + 2 )) . ( √x + 1 )/( √x – 1 )`

    `P = ( √x – 1 )/( √x ) . ( √x + 1 )/( √x – 1 )`

    `P = ( √x + 1 )/( √x )`

    `Vậy  P = ( √x + 1 )/( √x )`   với  `x > 0 ; x` $\neq$  `1`

Leave an answer

Browse

By answering, you agree to the Terms of Service and Privacy Policy.